2006
DOI: 10.1186/cc5115
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of furosemide regimens in neonates treated with extracorporeal membrane oxygenation

Abstract: Introduction Loop diuretics are the most frequently used diuretics in patients treated with extracorporeal membrane oxygenation (ECMO). In patients after cardiopulmonary bypass (CPB) surgery, the use of continuous furosemide infusion is increasingly documented. Because ECMO and CPB are 'comparable' procedures, continuous furosemide infusion is used in newborns on ECMO. We report on the use of continuous intravenous furosemide in neonates treated with ECMO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Van der Vorst et al [94] stated that tolerance of furosemide effect does not develop with prolonged diuretic exposure. It has been suggested that the tolerance to furosemide can be induced through different but complementary homeostatic mechanisms in the kidney [95,96].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Van der Vorst et al [94] stated that tolerance of furosemide effect does not develop with prolonged diuretic exposure. It has been suggested that the tolerance to furosemide can be induced through different but complementary homeostatic mechanisms in the kidney [95,96].…”
Section: Resultsmentioning
confidence: 99%
“…There are no indications that tolerance develops towards the diuretic effect of furosemide in hemodynamically unstable infants with volume overload after cardiac surgery with cardiopulmonary bypass, who are treated with a relatively aggressive diuretic regimen with furosemide. It is unlikely that the high furosemide dose was associated with renal toxicity [94]. Relatively high furosemide doses did not result in metabolic alkalosis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations